896 The Effect of a Simple Intervention on Emergency Department Breaches in Trauma and Orthopaedics Patients: A Multi-Cycle Audit in a District General Hospital. (19th August 2022) - Burnett-Jones, L; Greenwood, K; Mead, A; Eltagy, H; Elashry, S
Abstract: Aim: We present a re-audit of Emergency Department (ED) waiting times following an intervention to improve surgical bed flow with the aim of further reducing the number of Trauma and Orthopaedics (T&O) patients that breached the four-hour wait target. Method: An initial two-cycle closed-loop audit of ED waiting times of patients admitted under T&O was undertaken. Protocols were updated and new guidelines were synthesised and implemented in collaboration between the ED and T&O departments. This intervention reduced the number of patients that breached in ED and identified bed availability as the primary cause of these breaches. A third cycle was done. Posters were placed in key prescribing areas of the T&O department, detailing the need for 'to take-out' (TTO) prescriptions 'to be completed before 15:00 as after this time pharmacy will not dispense the prescription'. Data was collected retrospectively from clinical e-documentation. P-values were calculated by Fishers Exact test. Results: 57 patients were included in cycle 1 and 51 patients in cycle 2. ED breaches reduced from cycle 1 to cycle 2: 86% to 65% respectively (p < 0.05). In cycle 3, 42 patients were included, and breaches increased to 67% of patients, representing no significant change from cycle 2 (p > 0.05). The number of breaches due to a shortage of hospital beds increased from 45% in cycle 2 to 75% in cycle 3 (p < 0.05). Conclusion: Bed shortages remained the main cause for T&O admissions to breach in ED. Earlier completion of TTO prescriptions did not solve the problem.